Three Therapeutic Strategies: Cinacalcet, Paricalcitol or Both in Secondary Hyperparathyroidism Treatment in Hemodialysed Patients During 1-Year Observational Study—A Comparison - Zawierucha, Jacek; Malyszko, Jolanta; Malyszko, Jacek S.; Prystacki, Tomasz; Marcinkowski, Wojciech P.; Dryl-Rydzynska, Teresa (Frontiers in Endocrinology, 2019)
Introduction Secondary hyperparathyroidism is one of the common hormonal complication of chronic kidney disease. There are several therapeutic options for management of sHPT aiming at normalization of calcium-phosphorus balance and decrease of parathyroid hormone secretion. Objectives The aim of this retrospective, observational study was to assess the outcome of three most common therapeutic strategies of secondary hyperparathyroidism treatment with vitamin D receptor activator-paricalcitol, calcimimetic-cinacalcet or both agents administered together during in 12-months period. Methods 131 haemodialysed patients with uncontrolled parathyroid hormone secretion has been treated with intravenous paricalcitol (60 patients) or oral cinacalcet (50 patients). The third group (21 patients) received intravenous paricalcitol and oral cinacalcet administered simultaneously. Results In all groups, a significant decrease of iPTH level was observed, however in group treated with intravenous paricalcitol iPTH level decreased significantly higher than in group treated with cinacalcet and in the third one treated with paricalcitol and cinacalcet in parallel. The highest change of iPTH level was noticed after three months of observation. After this period the iPTH level was stabilized and remained on similar level till the end of observation. The level of safety is similar for all the strategies. No severe hypercalcemia or hypocalcemia was observed during the whole period of observation. Conclusions The results of this study show significant advantage of intravenous treatment with paricalcitol. Adding paricalcitol to the therapy with cinacalcet does not improve the outcomes of the treatment. In case of unsatisfactory results after the 3-months treatment, a possible continuation should be considered carefully. Treatment with intravenous paricalcitol should be considered in all haemodialysed patients with inadequate control of serum PTH level. sHPT treatment with cinacalcet should be considered in PD patients and when severe hypercalcemia occurs.